Research Progress on the Mechanism of Biochar and Microorganisms on Fraction Transformation of Heavy Metals in Farmland Soil - Feng JIANG; Zhiyuan LIN; Yuyao LUO; Miaoting ZHOU; Rongbo XIAO; Peng WANG; Fei HUANG (Guangdong nongye kexue)
The issue of heavy metal pollution in farmland soils has become increasingly severe, posing significant risks to crop productivity, food safety, and human health. In recent years, biochar has gained considerable attention as a remediation material due to its abundant raw material sources, straightforward production process, and remarkable ability to immobilize pollutants. Similarly, microbial remediation has emerged as a promising approach for addressing moderate and mild soil pollution, offering advantages such as high efficiency, environmental sustainability, and cost-effectiveness. The integration of biochar and microbial remediation combines the strengths of both strategies, demonstrating substantial potential in treating heavy metal-polluted soils. This review systematically evaluates the impact of different biochar types, microbial strains, and biochar-microorganism combinations on the transformation of heavy metal speciation in farmland soils. Studies indicate that most biochar materials, microorganisms, and their composites exhibit strong immobilization effects on heavy metals. Notably, the combined approach typically outperforms individual treatments in terms of metal passivation efficiency. Additionally, the mechanisms underlying biochar, microbial, and combined remediation techniques in altering metal speciation are thoroughly discussed. Biochar remediates contaminated soils through multiple pathways, including electrostatic adsorption, ion exchange, complexation with functional groups, precipitation, cation-π coordination, and redox reactions. Microbial remediation primarily relies on extracellular precipitation, surface adsorption, biotransformation, and intracellular accumulation. The synergistic biochar-microorganism approach enhances remediation efficacy by using the protective effect of biochar on microorganisms and microbial-induced modifications to the physicochemical properties of biochar. Finally, in terms of the co-remediation technology of biochar and microorganisms, the theoretical research and practical application in the field of heavy metal-contaminated soil treatment are prospected, which provides theoretical references for subsequent investigations.